2016
DOI: 10.1002/bit.26029
|View full text |Cite
|
Sign up to set email alerts
|

Newly identified bacteriolytic enzymes that target a wide range of clinical isolates of Clostridium difficile

Abstract: Clostridium difficile has emerged as a major cause of infectious diarrhea in hospitalized patients, with increasing mortality rate and annual healthcare costs exceeding $3 billion. Since C. difficile infections are associated with the use of antibiotics, there is an urgent need to develop treatments that can inactivate the bacterium selectively without affecting commensal microflora. Lytic enzymes from bacteria and bacteriophages show promise as highly selective and effective antimicrobial agents. These enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…We have previously identified CD11 to be an effective lytic enzyme with N -acetylmuramoyl-L-alanine amidase activity against vegetative cells of C. difficile at mid-log phase 32 . To test the lytic activity of CD11, the killing assay was performed in both PBS and growth medium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously identified CD11 to be an effective lytic enzyme with N -acetylmuramoyl-L-alanine amidase activity against vegetative cells of C. difficile at mid-log phase 32 . To test the lytic activity of CD11, the killing assay was performed in both PBS and growth medium.…”
Section: Resultsmentioning
confidence: 99%
“…For example, CD27L is a potent endolysin against C. difficile with zinc-dependent N -acetylmuramoyl-L-alanine amidase activity 30 31 . We previously identified an autolysin CD11 with similar activity to CD27L 32 . CD11 reduces the viability of mid-log phase C. difficile cells by 3–4 log units in 3 h in aqueous buffer and is active against a wide range of clinical isolates, making it attractive for in vivo therapeutic use 32 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very little is known about the PG-degrading enzymes in C. difficile . Acd, a PGH with N -acetylglucosaminidase activity, and two proteins exhibiting N -acetylmuramyl- l -alanine amidase activity, the CD11 and CDG enzymes, have been identified, but their physiological functions have not yet been investigated ( 33 , 34 ). In addition, SleC, a spore cortex lytic enzyme with LT activity, has been shown to be essential for germination of C. difficile spores ( 35 , 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…Keeping in mind that virulence if often tied to resistance [68], the emergence of highly virulent strains of this bacteria and a reduced susceptibility to antibiotics has led to the development of MDR strains [69]. Fortunately, recent studies have shown that certain lytic enzymes from bacteria and bacteriophages can act as highly selective and effective antimicrobials [70]. These enzymes can be delivered without a traditional targeted delivery system and yet still remain selective against a wide range of C. difficile, preserving the normal gut flora.…”
Section: Targeted Drug Delivery Systemsmentioning
confidence: 99%